The antiosteoporotic effect of oxymatrine compared to testosterone in orchiectomized rats - Anwaar M. Shaban; Eman A. Ali; Sara G. Tayel; Sara Kamal Rizk; Dalia F. El Agamy (Journal of Orthopaedic Surgery and Research)
Abstract Background Castration of adult male rats led to the development of osteoporosis. Oxidative stress and inflammatory factors have been identified as potential causative factors. Notably, oxymatrine (OMT) possesses potent anti-inflammatory and antioxidant activities. This study aims to elucidate the antiosteoporotic effects of OMT compared to testosterone in an orchiectomized (ORX) rat model of osteoporosis. Methods A total of 60 Wistar male rats were divided into the following groups: control (CTRL), surgery + no orchiectomy (SHAM), ORX, ORX + testosterone, and ORX + OMT. Urinary deoxypyridinoline (DPD), calcium (Ca), and phosphorus (P), as well as serum testosterone, parathormone (PTH), alkaline phosphatase (ALP), osteocalcin, N-telopeptide of type I collagen (NTX I), tartrate resistance acid phosphatase (TRAP), and total Ca and P levels were evaluated. Bone was assessed for malondialdehyde (MDA), reduced glutathione (GSH), interleukin 6 (IL-6), Kelch-like ECH-associated protein 1 (Keap1), nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase 1 (HO-1) expression, and receptor activator of nuclear factor κB ligand/ osteoprotegerin (RANKL/OPG) ratio. Bone dual-energy X-ray absorptiometry (DEXA) scan and histological and immunohistochemical studies were performed. Results Testosterone or OMT treatment ameliorated the reduced bone mineral density (BMD) and bone mineral content (BMC) in the DEXA scan and the changes in PTH and Ca levels. Compared to the ORX group, bone formation, and turnover markers were also significantly reversed in the treatment groups. Treatment with testosterone or OMT significantly reduced bone MDA, IL-6, Keap1, RANKL, and RANKL/OPG ratio, and significantly elevated bone GSH, Nrf2, and HO-1. Moreover, testosterone or OMT treatment has restored cortical bone thickness and osteocyte number and reduced bone levels of TNF-α in ORX rats. Consequently, treatment with either testosterone or OMT exhibited nearly equal therapeutic efficacy; however, neither of them could normalize the measured parameters. Conclusion OMT treatment showed equal efficacy compared to testosterone in ameliorating osteoporosis in ORX rats, possibly by improving some inflammatory and oxidative stress parameters.